‘The Social Brain’: The Human Brain Communicating Through Social Experience - Berenson, Alonit; Keidar, Daniella (Kultura-Społeczeństwo-Edukacja, 2016)
This article suggests an overview of the social brain, evaluation of local and global groups and the relationship between the individual, the brain and society. Emphasis is put on individual and collective identity and on the shaping of public opinion through the media and on examining future developments that will mold social trends and most importantly, whether it is possible to promote the evolution of a better society that is built on cooperation, reciprocity, altruism, understanding, attention, sensitivity, values and a high level of ethical functioning. The development of thinking, planning and new revelations have increased the need for engagement and connection with others. The human brain has developed self-interest thinking. Utilitarian calculations have become a part of humanity's engagements. Group relationships are essential for survival, care, concern and security. The product of the dichotomous existence of man and society: egoism versus cooperation and altruism. In order to survive as an individual in the group and as a group, the social brain developed and shaped thinking procedures of framing and instincts in patterns of feelings and emotions. The influencing messages of environmental sources which exist in the public sphere impact by pass the human brain through "mirror" nerves, stereotype thinking and collective and evolutionary memory, fulfilling basic motivation needs, creating belonging, love and appreciation. For instance, the media that uses these groups shared involvement feelings and collective identity to shape by means of "framing" the public opinion and way of thinking, and by that shape the perception of the reality.